The book bandit : a mystery with geometry - Thielbar, Melinda (Thielbar, Melinda. Manga math mysteries, 2011)
When the public library offers a prize for figuring out how a "book monster" sculpture was fit in through a small window in their Reader's Corner, the students of Sifu Faiza's Kung Fu School use geometry to solve the mystery.